Determinants of the exchange rate, its volatility and currency crash risk in Africa's low and lower middle-income countries - Anjelo Okot; Annina Kaltenbrunner; Daniel Perez Ruiz (European Investment Bank (EIB), 2022)
This paper investigates the determinants of nominal exchange rates, their volatility, and crash risk in Africa's lower and lower-middle income countries (LLMICs). It combines macro-panel estimations for 15 African LLMICs with floating or lightly managed exchange rates, with insights from 13 semi-structured interviews with 17 foreign exchange market participants in six case study countries. It shows the important role African LLMICs' distinct productive and export structure, concentrated in a few agricultural and mineral-based commodities, and recent financial integration for exchange rate determination. In particular, whereas productive factors such as terms of trade, export concentration, and export prices are found to have a significant impact on the exchange rate level and volatility, financial factors including the interest rate differential, international market conditions, and short-term financial flows, matter for the likelihood of currencies to experience sudden and large exchange rate movements.
Keywords: 330